Investigation into traffic flows on high intensity streets of Vilnius city - Žiliūtė, Laura; Laurinavičius, Alfredas; Vaitkus, Audrius (Transport, 2010)
The measurements and analysis of traffic intensity were performed in the capital city – Vilnius, the largest urban area in Lithuania. Vilnius is a centre of business, industry and tourism, and therefore traffic intensity remains the highest in this part of the country. The intensity of vehicle traffic is not only generally calculated but also simultaneously classified which means is divided predefining vehicles into beforehand established categories. Data on traffic flows are used in a road maintenance program for calculating and assessing air pollution, ensuring traffic safety, regulating traffic flows etc. The article presents the methods for measuring traffic intensity which are and were used for calculating traffic intensity not only in the streets of Vilnius but also across Lithuania. Data on vehicle intensity and classification are collected either using technologies (loop and tube detectors, counters and video detectors) or expressing them visually. The article presents the dynamics of changes in the traffic volume on the roads of Lithuania for the period 2000–2009. Also, this article examines traffic intensity of all transport means, including trucks in the permanent traffic volume measuring stations that were installed near the roads in Vilnius zone (data on traffic for the period 2005–2009) and the streets of Vilnius city (data on traffic for the period 2007–2009). Data on traffic intensity were obtained by the Road Research Laboratory of the Road Department of Vilnius Gediminas Technical University in cooperation with the State Enterprise Transport and Road Research Institute (TRRI).First published online: 10 Feb 2011